Cross-cultural adaptation of the instrument "Family Needs Questionnaire" Adaptación transcultural del instrumento Family Needs Questionnaire Adaptação transcultural do instrumento Family Needs Questionnaire - Edilene Curvelo Hora; Regina Márcia Cardoso de Sousa (Universidade de São Paulo, 2009)
This is a quantitative methodological development study on the cross-cultural adaptation of the "Family Needs Questionnaire" (FNQ), which is a structured instrument developed in the United States to measure the perceived needs of family members after the Traumatic Brain Injury (TBI) of a relative. This instrument aims to identify important needs presented by family members, whether met or not. The FNQ translation and adaptation followed a particular method, which permitted to achieve semantic, idiomatic, cultural and conceptual equivalence of the instrument version labeled in Portuguese as "Questionário de Necessidades da Família". The results of the questionnaire application to 161 family members showed that the instrument content is valid to measure the needs of families of patients with TBI in the Brazilian context. Se trata de estudio cuantitativo de desarrollo metodológico sobre la adaptación transcultural del Family Neds Questionnaire (FNQ), instrumento estructurado, desarrollado en los Estados Unidos, para medir las necesidades percibidas por los miembros de la familia, después del trauma cráneo encefálico (TCE) de un familiar. El propósito de ese instrumento es identificar necesidades atendidas y no atendidas importantes para los familiares. La traducción y adaptación del FNQ siguieron una metodología propia que permitió alcanzar equivalencia semántica, idiomática, cultural y conceptual del instrumento traducido, denominado, en portugués, Cuestionario de Necesidades de la Familia. Los resultados de la aplicación del cuestionario en 161 familiares mostraron que el contenido del instrumento es válido para medir, en nuestro medio, las necesidades de los familiares que tiene personas con TCE. Trata-se de estudo quantitativo de desenvolvimento metodológico sobre a adaptação transcultural do Family Needs Questionnaire (FNQ), instrumento estruturado, desenvolvido nos Estados Unidos, para medir as necessidades percebidas pelos membros da família, após o trauma cranioencefálico (TCE) de um familiar. O propósito desse instrumento é identificar necessidades atendidas e não atendidas importantes para os familiares. A tradução e adaptação do FNQ seguiram metodologia própria que permitiu alcançar equivalência semântica, idiomática, cultural e conceitual do instrumento traduzido, denominado, em português, Questionário de Necessidades da Família. Os resultados da aplicação do questionário em 161 familiares mostraram que o conteúdo do instrumento é válido para medir, em nosso meio, as necessidades dos familiares que têm pessoas com TCE.